Pengaruh Perekrutan, Seleksi, Penempatan Kerja dan Budaya Kerja Terhadap Kinerja Pegawai BPR Chandra Mukti Artha - Inayat Hanum Indriati; Padrul Jana (Universitas Batanghari Jambi, 2022)
Employees who have good performance can not happen in a short time, but through a process. To obtain employees who have good performance, companies must pay attention to the abilities or competencies of employees. Therefore, it is necessary to manage Human Resources (HR) in this case are employees, which include planning human resources, procurement, directing, developing, maintaining and dismissing. The objectives of the study were (1) to determine the effect of recruitment on employee performance, (2) to determine the effect of selection on the performance of BPR Chandra Mukti Artha employees, (3) to determine the effect of job placement on employee performance at BPR Chandra Mukti Artha, (4) to determine the influence of work culture. on the performance of BPR Chandra Mukti Artha employees and (5) knowing the effect of recruitment, selection, work placement and work culture on the performance of BPR Chandra Mukti Artha employees simultaneously. The research sample is the employees of BPR Chandra Mukti Artha with a total of 46 people, selected by population sampling technique. Data collection techniques with questionnaires. Data analysis technique with multiple linear regression consisting of F test, t test and coefficient of determination, where previously carried out classical assumption test which includes normality test, multicollinearity test and heteroscedasticity test. The results showed that (1) Recruitment had a positive effect on employee performance, (2) Selection had a positive effect on employee performance, (3) Job placement had a positive effect on employee performance, (4) Work culture positive effect on employee performance and (5) Recruitment, selection, work placement and work culture simultaneously affect employee performance. The conclusion of this study is that the better employee recruitment, employee selection, work placement and work culture, the better employee performance will be. Vice versa, if employee recruitment, employee selection, work placement and work culture are not good, then employee performance will also be low.